A Study On Prevalence Of Thyroid Dysfunction In Rheumatoid Arthritis Patients Attending Outpatient Department Of A Tertiary Care Hospital (Journal of Pharmaceutical Negative Results, 2022)
Background:RA is a systemic autoimmune disorder characterized by symmetrical, inflammatory, deforming polyarthritis affecting small and large peripheral joints with associated systemic disturbance such as vacuities and nodules. The prevalence of thyroid dysfunction in rheumatoid arthritis is 10-15% which is high in previous studies2, 3 .This study shows the prevalence of thyroid dysfunction in RA patients in indian population .Aims:A study on prevalence of thyroid dysfunction in rheumatoid arthritis patients attending outpatient department of a tertiary care hospitalMaterials and Methods:.The study was a case control study involving 50 rheumatoid arthritis patients (8 male and 42 female) .The conditions which can alter thyroid profile were excluded from the study population at the time of selection and sex matched healthy subjects were taken as controls .Thyroid function test were done in all patients and controls. In patients who were found to have thyroid dysfunction TPO antibodies were done.SPSS 24was used for statistical analysis of resultsResults: Prevalence of thyroid dysfunction is higher in patients with rheumatoid arthritis.